Pengaruh Penggunaan Media Gambar Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas IV SD Negeri 030296 Parbakalan Kabupaten Dairi Tahun Pembelajaran 2022/2023 - Rinawati Sinaga; Johari Manik; Tianggur Medi Napitupulu (Jurnal Pendidikan Agama dan Teologi, 2023)
The aim of this research is to determine the effect of using image media on the learning motivation of Christian Religious Education for Grade IV Students at State Elementary School 030296 Parbakalan, Dairi Regency, Academic Year 2022/2023. The research method used is a quantitative research method. The population is all students in class IV of SD Negeri 030296 Parbakalan Dairi Regency for the 2022/2023 academic year who are Christians, totaling 40 people. Data was collected using a positive closed questionnaire with 40 items, namely 20 items for variable /2023: 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.560 > rtable(a=0,05,n=40) = 0.312. b) Testing a significant relationship obtained a value of tcount= 4.164 > ttabel(a=0,05,dk=n-2=38)= 2.021. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂="38.52"+0.42X. b) Regression coefficient of determination test (r2) = 31.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=18, dk denominator=n-2=40-2=38) namely 17.34 > 1.51. Thus Ha is accepted and H0 is rejected.